Sustainability of Lake Timbang Bunga Pengantin in Sungai Sorik, Kuantan Hilir Seberang District, Kuantan Singingi Regency, Riau - Ridwan Manda Putra Manda Putra; Sukendi Sukendi; Yusni Ikhwan Siregar; Lilis Kurnia; Ade Yulindra (ECOTONE, 2021)
Lake Timbang Bunga Pengantin, an oxbow lake, has been a favorite tourist destination in Kuantan Singingi Regency in the last decade. The lake of 12 ha in area were used for multi purposed locally livelihood indluding tradisional rice field in the bank of the lake, irigation, fishing ground, fish cage culture, floating resdtaurant and water attraction tourism. As such the lake faced heavy burdens and could interferred the sustainability of the lake. To overcome the environmental problem for sustainability of the ecosystem,a management sustainable strategy need to be formulated with multi criteria of consideration. The present study applied multi-dimentional scaling (MDS) approach following RapLake. The result showed that, the sustainability state of Danau Timbang Bunga Pengantin based on ecology, technology, regulation, were 60,6%,  62,8 %, 70,2%,  respectively, which categorized fairly sustainable, while based economy and sociocultural categorized less sustainable which index of  35.3 % and 44,5 %,  respectively. It revealed that 11 atributes namely; water fertility of lake, fish biodiversity, water condition, tourist potency, capital, fishing dependency, infrastructure, law enforcement, fertilizing of rice field, social  conflict and community empowerment, which driven factors of the management of the lake. The management strategy should start on developing supporting tourism facilities such as econo-lodging, home stay, new attraction, road improvement and amenities. Further the management develop a locally unique attraction and increase local knowledge. Another aspect of important was promotion of the tourist destination through media.